The Role of Leadership Strategy in Facing Blockchain Technology in the Defense Industry in Indonesia - Hariyantana Aygy Yolanda; Khaerudin , Khaerudin; George Royke Deksino (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The development of a robust defense industry is crucial for national security, requiring a balance between nationalism, strategic leadership, and the integration of cutting-edge technologies such as blockchain. This paper explores the significance of blockchain in revolutionizing the Indonesian defense industry, emphasizing its potential to enhance transparency, accountability, security, and efficiency. The research employs descriptive qualitative methods, utilizing diaries, literature reviews, and various references. The leadership strategy for effective blockchain integration is outlined, including a clear vision, understanding of blockchain technology, proper implementation, leader commitment, and adaptability. The defense industry's ability to adapt to evolving blockchain technology is emphasized, requiring a competent team and a culture supporting innovation. Leadership strategies are further detailed, emphasizing the importance of research and development, partnerships with other industries, and socialization and education to stakeholders. These strategies aim to increase competence, accelerate development, enhance collaboration, and build trust in blockchain technology within the defense industry